Multiple bacteriosis, with special reference to spoilage bacterium Shewanella putrefaciens, in cage-cultured barramundi perch in Malaysia - Subasinghe, R. P.; M., M. Shariff
An incidence of multiple bacteriosis that caused heavy mortality in cage-cultured barramundi perch Lates calcarifer during May-July 1991 in the Pulau Ketam estuary in west coast of Malaysia was investigated. All fish showing hemorrhagic dermatitis were infected with Pseudomonas anguilliseptica and Vibrio alginolyticus, and the spoilage bacterium Shewanella putrefaciens was consistently isolated from all sampled fish. High-density culture under suboptimal nutritional and environmental conditions, together with feeding on spoiled coarse fish, was considered to have initiated the epizootic.